Upaya Meningkatkan Kreativitas Anak Usia Dini Melalui Kegiatan Finger Painting pada Kelompok B di TK Diniyyah Kota Pekanbaru (Prosiding Keislaman dan Sains, 2025)
Creativity is the ability to create something new in the form of ideas and real work that is relatively different from what has existed before. Therefore, early childhood must be trained in the development of creativity. Therefore, researchers chose finger painting activities as one of the activities to develop children's creativity. Because in finger painting activities children can express their imagination directly, children are given the freedom to draw whatever the child thinks through the media provided. The purpose of this study was to improve early childhood creativity through finger painting activities in group B at Diniyyah Kindergarten, Pekanbaru City. In this study the authors used classroom action research with the subject of teachers and students in group B of TK Diniyyah Kota Pekanbaru. Researchers conducted 2 cycles, each of which consisted of planning, implementation, observation or observation and reflection stages in each cycle. By observing students during learning activities, researchers finally found that in Cycle I the percentage of children's creativity in finger painting activities was 60%. In Cycle II the percentage of children increased to 80%.
Keywords: Creativity; Finger Painting; Early Childhood